Spherical array system for high precision transcranial ultrasound stimulation and optoacoustic imaging in rodents. - Estrada, Héctor (IEEE Trans Ultrason Ferroelectr Freq Control, 2020)
Ultrasound can be delivered transcranially to ablate brain tissue, open the blood-brain barrier or affect neural activity. Transcranial focused ultrasound in small rodents is typically done with low-frequency single element transducers, which results in unspecific targeting and impedes the concurrent use of fast neuroimaging methods. Here we devised a wide-angle spherical array bidirectional interface for high-resolution parallelized optoacoustic imaging and transcranial ultrasound delivery (POTUS) in the same target regions. The system operates between 3 and 9 MHz, allowing to generate and steer focal spots with widths down to 130 μm across a field of view covering the entire mouse brain, while the same array is used to capture high resolution 3D optoacoustic data in real time. We showcase the system’s versatile beam-forming capacities as well as volumetric optoacoustic imaging capabilities and discuss its potential to non-invasively monitor brain activity and various effects of ultrasound emission.